2019
DOI: 10.1097/nur.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Nurse Specialist Preceptor Protocol

Abstract: Purpose: Develop an evidence-based clinical nurse specialist (CNS) preceptor protocol to enhance preceptor’s skills and effectiveness and strengthen the preceptor-preceptee relationship and outcomes. Description: An effective CNS preceptor is a key variable to quality, timely, and fiscally responsible CNS transition and retention. Most preceptors receive no formal education or skill development. Literature searched from the previous 10 years explored CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“… Zambrana et al (2019) study revealed significant negative correlations between role ambiguity and role practice, and they concluded their study by suggesting that a bank that emphasizes role conflict and role ambiguity of financial advisors may contribute to the job satisfaction of financial advisors, which in turn improves their role practice. Bloomingdale and Darmody (2019) discovered that there were more senior financial advisors than junior financial advisors among the study participants and suggested providing employees with clearer direction and work objectives to better understand the expectations of the bank and individual responsibilities to reduce role ambiguity and promote role practice. It was necessary to reduce role ambiguity and increase self-efficacy to promote role practice among managers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“… Zambrana et al (2019) study revealed significant negative correlations between role ambiguity and role practice, and they concluded their study by suggesting that a bank that emphasizes role conflict and role ambiguity of financial advisors may contribute to the job satisfaction of financial advisors, which in turn improves their role practice. Bloomingdale and Darmody (2019) discovered that there were more senior financial advisors than junior financial advisors among the study participants and suggested providing employees with clearer direction and work objectives to better understand the expectations of the bank and individual responsibilities to reduce role ambiguity and promote role practice. It was necessary to reduce role ambiguity and increase self-efficacy to promote role practice among managers.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…New CNSs often face reality shock during TTP as they recognize immense practice responsibilities combined with a steep learning curve 6,9,10 . There is a gap between theory and clinical practice for new CNS hires during TTP 10,11 . Factors such as loss of a previous peer group, stress, job dissatisfaction, and loss of control lead to attrition 12 .…”
Section: Significance Of the Problemmentioning
confidence: 99%
“…6,9,10 There is a gap between theory and clinical practice for new CNS hires during TTP. 10,11 Factors such as loss of a previous peer group, stress, job dissatisfaction, and loss of control lead to attrition. 12 Job stress and attrition can lead to reduced patient safety and quality.…”
mentioning
confidence: 99%
“…Isso mostra, mais uma vez, o quanto a ausência de uma metodologia e/ou instrumento para determinar se o profissional pode ser ou não preceptor pode tornar a aprendizagem do novo profissional insegura, envolvendo riscos assistenciais, além de comprometer o trabalho em equipe e impor dificuldades de adaptação aos novos colaboradores. (47) Outro ponto relevante o qual justifica que o instrumento é um ganho é que o preceptor que tem as competências necessárias influenciará positivamente as ações de qualidade e segurança nos processos que realizará. Além disso, irá melhorar o relacionamento com a equipe, gerando um ambiente de segurança psicológica não só com seu preceptor, mas também no meio em que está inserido, com o paciente, família e equipe.…”
Section: Discussionunclassified